Enraizamento de estacas de goiabeira (Psidium guajava L.) cultivares séculoXXI e paluma - Costa, Jussara Cristina Firmino da (2015)
Among the many strands that covers horticulture, seedling production has gained great prominence, by showing I came up as an alternative to increasing the employment level preventing migration. However, it is still little information about the determinations necessary for the production of quality seedlings. The objective of this research, to establish a protocol for rooting cuttings of guava (Psidium guajava L.) cultivars Século XXI and Paluma for the commercial production of seedlings. Three experiment were: 1) Rooting cuttings of guava 'paluma' in organic substrates under the action of rooting inducers; 2) Rooting of herbaceous cuttings and semihardwood guava Século XXI cultivar treated with different concentrations of IBA; 3) Use of IBA in rooting of guava stakes grow „Século XXI‟. The experiments were conducted in a greenhouse located in Nursery Fruticultura/DFCA/CCA/ UFPB. Thus, the experimental design adopted in all it was a completely randomized, with four, three and three replicates respectively, with 10 cuttings per plot. In experiment 1 the treatments consisted of five substrates (S1-25% CAC + 75% CO; S2-75% CAC + 25% CO; S3-50% CAC + 50% CO; S4-100% CO; S5-100 % CCS) at a concentration of 2000 mg L-1 IBA and RADIMAXI 20® . In experiment 2 treatments consisted of six concentrations of IBA (0.0, 0.0*, 1000, 1500, 2000 and 2500 mg L-1 ), the dose 0.0 concerning absolute control (planted directly without any treatment) and 0.0* relative to control (immersed in distilled water for 12 hours). In experiment 3 treatments were four immersion times in AIB solution (5, 10, 15 and 20 seconds) with a concentration of 2000 mg L-1 IBA. For the physical characterization of organic substrates Five formulations were made: S1) 25% CCS + 75% CO; S2) CAC 75% + 25% CO; S3) CAC 50% + 50% CO; S4) 100% CO; S5) 100% CAC. The seedlings were evaluated at: rooted cuttings (%) rooted cuttings without leaf (%), living Stakes rootless (%), cuttings with callus (%) sprouting (%), leaf retention (%) mortality (% ), number of roots, root length (cm), shoot fresh weight (g), shoot dry mass (g), fresh root mass (g) and dry mass of roots (g). Physical analysis of substrates were evaluated: dry density (Ds); total porosity (PT); aeration space (AS); easily available water (AFD); buffering water (AT); available water (AD); and remainder water (RA). For the conditions studied, it is concluded that in experiment 1 the substrate with formulation 25% rice bark + 75% organic compound (S1) provides a higher percentage of rooting, callus, sprouting and root dry mass, while reducing the proportion of mortality stakes and resets the percentage of live cuttings without roots, being mentioned for the propagation of herbaceous cuttings of guava 'Paluma' at a concentration of 2000 mg L-1 of AIB; and Radimaxi 20® at a concentration of 2000 mg L-1 of AIB, promotes the increase in the vegetative part of the cutting and stimulates callus formation; In experiment 2 herbaceous of guava stake is the most suitable for the propagation of guava plants grow twenty-first century; The contrast between absolute zero and the relative zero no significant difference; and the application of 2500 mg L-1 IBA provides the best characteristics in terms of rooting percentage, leaf retention, number of roots, fresh and dry weight of shoot and fresh and dry root in herbaceous cuttings of Psidium guajava L. 'Século XXI'; In experiment 3 the immersion time of the cuttings, 5 seconds at the concentration of 2000 mg L-1 IBA presents the best results in the propagation process of guava stakes 'Século XXI'. In physical analyzes it was concluded that the substrate comprises 50% carbonized rice husk + 50% organic compound (S3) having the most suitable physical characteristics, among substrates tested, as this formulation allows a possible supply to the plants if there is water stress and has the best feature of the dry density, which predicts other characteristics to the plant essences;